Ensuring the Validity of Accounts Receivable Through Five Audit Assertions - Chantika Mukti Ardi; M. Nur Abdullah Birton (Jurnal Akuntansi Indonesia, 2026)
Abstract Accounts receivable is an account with a high risk of material misstatement because it involves estimation and uncertainty of value. Therefore, Test of Controls through five audit assertions is important to ensure the reliability of internal control. However, studies on how auditors interpret and perform tests of controls on accounts receivable are still limited. This study aims to uncover auditors’ understanding in assessing the reliability of internal control over accounts receivable through five audit assertions using Paul Ricoeur’s hermeneutic approach. The method used is qualitative interpretive with analysis at the semantic, reflective, and existential stages. The results show that testing of controls is not only technical, but also interpretative. Auditors consider context, risk, and professional judgment in assessing the effectiveness of controls, resulting in differences in interpretation among auditors.